'FLOWER OF THE LILY': LATE-MEDIEVAL RELIGIOUS AND HERALDIC SYMBOLISM IN PARIS, BIBLIOTHÈQUE NATIONALE DE FRANCE, MS FRANÇAIS 146. (29th August 2014) - Caldwell, Mary Channen
<x content-type="archive" xml:space="preserve">Abstract</x> Paris, Bibliothèque nationale de France, MS français 146 (fr. 146), a manuscript well known for its inclusion of the Roman de Fauvel, also provides an important, albeit understudied, contribution to the history surrounding the allegorical 'flower of the lily', or fleur-de-lis – a floral symbol central to fourteenth-century theology and French royal heraldry. In medieval France, the fleur-de-lis emerges through text and music as a symbol capable of invoking, and being invoked by, the Holy Trinity, the Virgin Mary and the Virtues, all in the interest of supporting the religious and monarchical well-being of France. This study argues that the persistent return to the fleur-de-lis throughout the dits, the Chronique metrique and most especially the music and text of Fauvel in fr. 146 offers a necessary link between sacred and heraldic symbology both within the manuscript as well as within the larger historical development of this allegorical flower.